1987
DOI: 10.1038/326805a0
|View full text |Cite
|
Sign up to set email alerts
|

Sliding movement of single actin filaments on one-headed myosin filaments

Abstract: The myosin molecule consists of two heads, each of which contains an enzymatic active site and an actin-binding site. The fundamental problem of whether the two heads function independently or cooperatively during muscle contraction has been studied by methods using an actomyosin thread, superprecipitation and chemical modification of muscle fibres. No clear conclusion has yet been reached. We have approached this question using an assay system in which sliding movements of fluorescently labelled single actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
162
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(173 citation statements)
references
References 17 publications
11
162
0
Order By: Relevance
“…3A), and myosin sometimes dissociated from the actin filament. These results are consistent with the in vitro motility assay (29) and highlight the critical role of the electrostatic interaction. The reason for the loss of motility is now clearly understood on the basis of the energy landscape (Fig.…”
Section: Resultssupporting
confidence: 80%
“…3A), and myosin sometimes dissociated from the actin filament. These results are consistent with the in vitro motility assay (29) and highlight the critical role of the electrostatic interaction. The reason for the loss of motility is now clearly understood on the basis of the energy landscape (Fig.…”
Section: Resultssupporting
confidence: 80%
“…It is known, for example, that the affinity of single-headed myosin for actin is about an order of magnitude lower than that of double-headed myosin (1). However, in vitro motility assays have shown that single-headed myosin II molecules (2,3) and single isolated myosin heads (4,5) are able to produce force and movement, indicating that any cooperative aspect is not essential for function. An alternate possibility is that the dimeric structure of myosin is required solely to generate an a-helical coiled-coil tail.…”
mentioning
confidence: 99%
“…Rhodamine-phalloidin binds to actin filaments assembled in Mg > and KC1 with a I:1 stoichiometry and a dissociation equilibrium constant of 10 20 nM [15], and phalloidin itself appears to have a 5-to 10-fold higher affinity [23]. Rhodamine phalloidin is commonly used to label actin-containing filaments in cells and extracts of cells, and actin filaments labelled with the fluorescent deriwttive of phalloidin, tetramethyl rhodamine-phalloidin, can move on tethered myosin in in vitro motility assays [18,24]. It has been proposed that hydrolysis of ATP on filamentous actin might be an essential step in the mechanism of chemo-mechanical transduction in contracting muscle fibers [3,4,11,12].…”
Section: Discussionmentioning
confidence: 99%